Incidencia del liderazgo y valores en el comportamiento de los estudiantes del tercer año de bachillerato del Colegio Militar ¨Tcrn. Lauro Guerrero¨ de la ciudad de Loja, periodo 2010 – 2011. Lineamientos alternativos - Torres Palacios, Manuel Antonio (2012)
The present work of investigation was oriented to know the incidence the leadership and values in the behavior of the students of the Third year of Baccalaureate of the Military School “Tcrn. Lauro Guerrero”, of the city of Loja, during period 2010-2011 and to propose alternative guidelines, to overcome the problems detected by means of the investigation. The methods used in the investigation process were: inductive, deductive and descriptive the scientist, which guided the research process, as technical the survey was used the same that was applied to professors and students of the third year of Baccalaureate of the COMIL. After the analysis and interpretation of results one reached the conclusion that the leadership that know and practice in the COMIL, is the authoritarian one, the same that although it allows to maintain the discipline in the Institution, but with one lowers acceptance of the students which affects its behavior significantly. The predominant values that the students of the third year of Baccalaureate of the Military School know and practice are: honor, discipline, loyalty, honesty and corps esprit that are owned by the Institution, but that leaves a side other values that also are important in the integral formation of the students.